Design Optimization of a Hybrid Steam-PCM Thermal Energy Storage for Industrial Applications - René Hofmann; Sabrina Dusek; Stephan Gruber; Gerwin Drexler-Schmid (Energies, 2019)
The efficiency of industrial processes can be increased by balancing steam production and consumption with a Ruths steam storage system. The capacity of this storage type depends strongly on the volume; therefore, a hybrid storage concept was developed, which combines a Ruths steam storage with phase change material. The high storage capacity of phase change material can be very advantageous, but the low thermal conductivity of this material is a limiting factor. On the contrary, Ruths steam storages have fast reaction times, meaning that the hybrid storage concept should make use of the advantages and compensate for the disadvantages of both storage types. To answer the question on whether this hybrid storage concept is economically feasible, a non-linear design optimization tool for a hybrid storage system is presented. From a preliminary approximation, the results show that the costs of hybrid storage can be reduced, in comparison to a Ruths steam storage with the same storage capacity. Furthermore, a possible hybrid storage design for a real industrial implementation is discussed. Based on further analyses, it was shown that under certain conditions, the retrofitting of a conventional Ruths steam storage to a hybrid storage can be advantageous and cost-effective, compared to an additional Ruths steam storage.